The Relationship Between Federal Government Revenue and Spending: Empirical Evidence from Asean-5 Countries - Zulkefly Abdul Karim; Norain Mod Asri; Azrina Al-Hadi Abdullah; Antoni Antoni; Zetty Zahureen Mohd.Yusoff (Universitas Islam Indonesia, 2006)
The main objectives of this paper is to examine the long run relationship between total expenditure, revenue (tax and nontax) and economic growth in ASEAN-5 countries namely by Malaysia, Indonesia, Thailand, Singapore and Philippines. According to the prior studies, there are several hypotheses to explain the relationship between revenue and spend-ing such as (1) spend-revenue hypotheses, (2) revenue-spend hypotheses and (3)bi-directional causality hypotheses. To test the validity of these hypotheses, this study will util-ize a cointegration and variance decomposition analysis. Based on empirical evidence, we can concluded that the existence of long run relationship between government spending, revenue (tax and non tax) and economic growth for all ASEAN-5 countries. The result of variance decomposition also shows that the strong influence on expenditure to revenue in countries namely Malaysia, Indonesia and Philippines, which support the ‘spend-revenue hypotheses. Meanwhile, for Thailand and Singapore the budget decision driven by revenue side which support the ‘revenue-spend hypotheses’. In addition, public expenditure plays no role to stimulate economic growth in Malaysia, Thailand, Singapore and Philippines, except for Indonesia. Key words: Fiscal economics; Wagner law; cointegration test; variance decomposition